Differences between Soil Ammonium and Nitrate Spatial Pattern in Six Plant Communities. Simulated Effect on Plant Populations - Gallardo, Antonio; Paramá, Rocio; Covelo, Felisa (Plant and Soil, 2005)
Geostatistical descriptions of soil heterogeneity patterns for plant communities are abundant in literature, however there is no information on the consequences of diﬀerent soil spatial patterns on resource availability for plant populations. Conditional simulations on the spatial distribution of soil NH4–N and NO3–N were carried out in order to study the eﬀect of contrasted patch sizes on nitrogen availability for individuals with increasing root system size. The semivariogram range (an indication of patch size) for soil NH4–N and NO3–N in six plant communities was found to be very variable, and was higher for soil NH4– N than for soil NO3–N in each community. A positive correlation was observed between organic matter and NH4–N spatial ranges in the six plant communities, but not between NO3–N and NH4–N. Probabilities of ﬁnding a high soil N concentration within simulated plant populations depended on N patch size and root system size. Thus, a population taking up NH4 –N (higher spatial range values) would be more heterogeneous (i.e. Individuals will have diﬀering probabilities of ﬁnding a high soil N concentration) than the same population taking up NO3–N. Likewise, a seedling population taking up NH4–N or NO3–N would be more heterogeneous than a large tree population in the same area, where individuals would have similar probability of ﬁnding a high soil N concentration. These results showed that the spatial patch size of limiting resources has important consequences at the population level, since it determines the probability of ﬁnding a favourable site and therefore diﬀering performances of individuals within a population.
Keywords: geostatistics; plant populations; root system size; Soil; soil ammonium; soil heterogeneity; Soil nitrate

Differences between Soil Ammonium and Nitrate Spatial Pattern in Six Plant Communities. Simulated Effect on Plant Populations - Gallardo, Antonio; Paramá, Rocio; Covelo, Felisa (Plant and Soil, 2005)
Geostatistical descriptions of soil heterogeneity patterns for plant communities are abundant in literature, however there is no information on the consequences of diﬀerent soil spatial patterns on resource availability for plant populations. Conditional simulations on the spatial distribution of soil NH4–N and NO3–N were carried out in order to study the eﬀect of contrasted patch sizes on nitrogen availability for individuals with increasing root system size. The semivariogram range (an indication of patch size) for soil NH4–N and NO3–N in six plant communities was found to be very variable, and was higher for soil NH4– N than for soil NO3–N in each community. A positive correlation was observed between organic matter and NH4–N spatial ranges in the six plant communities, but not between NO3–N and NH4–N. Probabilities of ﬁnding a high soil N concentration within simulated plant populations depended on N patch size and root system size. Thus, a population taking up NH4 –N (higher spatial range values) would be more heterogeneous (i.e. Individuals will have diﬀering probabilities of ﬁnding a high soil N concentration) than the same population taking up NO3–N. Likewise, a seedling population taking up NH4–N or NO3–N would be more heterogeneous than a large tree population in the same area, where individuals would have similar probability of ﬁnding a high soil N concentration. These results showed that the spatial patch size of limiting resources has important consequences at the population level, since it determines the probability of ﬁnding a favourable site and therefore diﬀering performances of individuals within a population.
Keywords: geostatistics; plant populations; root system size; Soil; soil ammonium; soil heterogeneity; Soil nitrate

Soil nitrogen heterogeneity in a Dehesa ecosystem - Gallardo, A; Rodriguez-Saucedo, J J (Plant and Soil, 2000)
The Dehesa are savannah-like ecosystems that occupy extensive areas in the mediterranean regions of Southern Spain and Portugal. The changes in the soil nitrogen (N) potential mineralisation rate, microbial biomass-N and available mineral N in soils were studied over 1 year in a Dehesa ecosystem, in the SW of Spain. The temporal variability of soil samples was compared by using the coefficient of variation of samples taken on a monthly basis. Spatial variability of the soil samples was measured by comparing the variograms generated with geostatistical techniques. The potential N mineralisation reached a maximum in the spring and summer samples, and a minimum in the autumn. However, the soil NHC 4 , NO 3 and microbial biomass-N showed maximum levels in winter, compared with minimum levels in the spring and summer. The potential mineralisation rate showed a higher temporal variability in the samples taken under tree canopies, due to highest maximum and similar minimum levels reached during the sampling period. The potential mineralisation rate, microbial biomass-N and soil mineral N were higher under the tree canopies than in the open grassland. The spatial distribution of the soil organicmatter and available NHC 4 was strongly influenced by tree canopy size. The semivariograms were adjusted to a spherical model, indicating a maximum NHC 4 variability at a certain distance from the tree crown diameter. The same was not the case for the spatial distribution of the soil NO 3 from the tree crown. Our results indicate that the tree component of a Dehesa ecosystem is a major influence in the spatial and temporal heterogeneity of soils.
Keywords: Dehesa; geostatistics; grassland; Quercus ilex; soil heterogeneity; soil nitrogen

Soil nitrogen heterogeneity in a Dehesa ecosystem - Gallardo, A.; Rodriguez-Saucedo, J. J. (Plant and Soil, 2000)
The Dehesa are savannah-like ecosystems that occupy extensive areas in the mediterranean regions of Southern Spain and Portugal. The changes in the soil nitrogen (N) potential mineralisation rate, microbial biomass-N and available mineral N in soils were studied over 1 year in a Dehesa ecosystem, in the SW of Spain. The temporal variability of soil samples was compared by using the coefficient of variation of samples taken on a monthly basis. Spatial variability of the soil samples was measured by comparing the variograms generated with geostatistical techniques. The potential N mineralisation reached a maximum in the spring and summer samples, and a minimum in the autumn. However, the soil NHC 4 , NO 3 and microbial biomass-N showed maximum levels in winter, compared with minimum levels in the spring and summer. The potential mineralisation rate showed a higher temporal variability in the samples taken under tree canopies, due to highest maximum and similar minimum levels reached during the sampling period. The potential mineralisation rate, microbial biomass-N and soil mineral N were higher under the tree canopies than in the open grassland. The spatial distribution of the soil organicmatter and available NHC 4 was strongly influenced by tree canopy size. The semivariograms were adjusted to a spherical model, indicating a maximum NHC 4 variability at a certain distance from the tree crown diameter. The same was not the case for the spatial distribution of the soil NO 3 from the tree crown. Our results indicate that the tree component of a Dehesa ecosystem is a major influence in the spatial and temporal heterogeneity of soils.
Keywords: Dehesa; geostatistics; grassland; Quercus ilex; soil heterogeneity; soil nitrogen

Local variations of ecosystem functions in Mediterranean evergreen oak woodland - Joffre, R; Rambal, S; Romane, F (Ann. For. Sci., 1996)
The spatial variation of ecosystem function was studied in a Quercus ilex coppice growing on hard limestone with low soil water availability. Spatial structures obtained from data on i) leaf area index, ii) leaf litterfall, and iii) leaf litter decay rate were compared. All these variables were sampled on 26 points located within a 30 x 30 m plot. Mean average leaf litterfall over 10 years (1984-1993) was 254 g.m-2. For each year, the semivariograms of leaf litterfall have been fitted using a spherical model. The values of the range parameter (indicating the limit of the spatial dependence) ranged from 6.4 to 10.3 m, very close to the value (9.2 m) of the range parameter obtained when fitting the semivariogram of mean leaf litterfall over 10 years. This result indicates the temporal persistence of the spatial pattern of leaf litterfall. The leaf area index (LAI) was estimated at the same points with a plant canopy analyzer. The mean value was 2.96 ± 0.30. The limit of spatial dependence for LAI was very close to that obtained for leaf litterfall (range = 8.5 m). The litter decomposition pattern was obtained through analysis of litter samples taken at the same points. The percentage of ash-free litter mass remaining (LMR) estimated using near-infrared reflectance spectroscopy indicates the stage of decomposition. It decreased strongly between the surface (mean value 85.6%) and the subsurface layers (mean value 63.4%). The two semivariograms can be described by spherical models, the sill being reached at a range of 21.4 and 18.7 m for the surface and subsurface layers, respectively. The two variables directly related to the structure of the canopy (LAI and leaf litterfall) exhibited close spatial dependence and differed from the soil process-related variables (stage of decomposition) whose ranges were approximately double. These geostatistical analyses show promise for use in developing hypotheses concerning the spatial scale of process-pattern interactions.
Keywords: decomposition; geostatistics; leaf area index; litterfall; local variation; Quercus ilex